2014
DOI: 10.1093/hmg/ddu739
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to maternal smoking and offspring DNA methylation across the lifecourse: findings from the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: Maternal smoking during pregnancy has been found to influence newborn DNA methylation in genes involved in fundamental developmental processes. It is pertinent to understand the degree to which the offspring methylome is sensitive to the intensity and duration of prenatal smoking. An investigation of the persistence of offspring methylation associated with maternal smoking and the relative roles of the intrauterine and postnatal environment is also warranted. In the Avon Longitudinal Study of Parents and Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
371
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(418 citation statements)
references
References 67 publications
41
371
4
2
Order By: Relevance
“…13 Others have demonstrated that these same methylation sites differed in the offspring of women who smoked during pregnancy, compared to offspring of non-smokers. 12,28 Prior studies demonstrating associations between smoking and AHRR DNA methylation used epigenome-wide methylation assays designed to discover previously unknown associations. 12,13 Given the results of these prior studies demonstrating that AHRR DNA methylation is modifiable during pregnancy, 12 we chose AHRR as a candidate gene to conduct a hypothesis-driven study of perinatal predictors of AHRR DNA methylation in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…13 Others have demonstrated that these same methylation sites differed in the offspring of women who smoked during pregnancy, compared to offspring of non-smokers. 12,28 Prior studies demonstrating associations between smoking and AHRR DNA methylation used epigenome-wide methylation assays designed to discover previously unknown associations. 12,13 Given the results of these prior studies demonstrating that AHRR DNA methylation is modifiable during pregnancy, 12 we chose AHRR as a candidate gene to conduct a hypothesis-driven study of perinatal predictors of AHRR DNA methylation in cord blood.…”
Section: Discussionmentioning
confidence: 99%
“…We use models adapted from Richmond et al [17]. For each CpG site, we used a linear mixed model with random intercept of individual and the following structure for individual i at time point j (j = 1 at baseline, j = 2 at follow-up) to model the methylation:…”
Section: Longitudinal Analyses: Baseline To Follow-upmentioning
confidence: 99%
“…These studies are an important next step in the understanding of the mechanisms of methylation [14]. To our knowledge, there have been only three reports investigating smoking and methylation with repeated measures: two candidate locus studies, one focusing on a small group of young women [15] and another on a small group of individuals attempting to quit smoking [16]; and a family-based study focused on maternal smoking [17]. Studies which cover larger sample sizes and different life stages are needed to better understand the effect of smoking on methylation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from the Avon Longitudinal Study of Parents and Children has demonstrated that prenatal maternal smoking affects epigenetic changes in DNA methylation in the offspring, with persistence of the DNA methylation changes into adolescence. 24 Although research in this area is in the early stages, the long-term impact of parental smoking on the offspring epigenome may underlie part of the atherogenic process.…”
Section: Article See P 1239mentioning
confidence: 99%